Ответы и объяснения

2012-03-02T19:49:24+04:00

1) 9x²-6x+1-4=0  

9x²-6x-3=0

D=b²-4ac

D=36+108=144

 x1=6+12/18=1

х2=6-12/18=-6/18=-1/3

 

2)  (5x +7)² - 9 = 0

25x²+70x+49-9=0

25x² +70x+40=0

D=b²-4ac 

D=4900-4000=900

x1=-70+30/50=-40/50=-0.8

x2=-70-30/50=-100/50=-2

  

 

3) (1/2x - 3)² - 1 = 0

(1/2x-2x1/2x3 -3)²-1=0

1/4x² -3x+9-1=0

 1/4x²-3x+8=0

 D=b²-4ac 

D= 9-9=0

x1= -b/2a=3/2*(1/4)=3/(1/2)=6

 

4) 1/9x²+10/3x+25-16=0
1/9x²+10/3x+9=0 
1/3x²+10x+3=0

D=100-4=96=( 4 корня из 6 ) 

 

 

 

 

 

 

2012-03-02T20:01:31+04:00

1. 9x²-6x+1-4=0

  9x²-6x-3=0

D=(-6)²-4*9*(-3)=36+108=144=12²

x_{1} = (6-12)/2*9=-6/18=-1/3

  x_{2} = (6+12)/18=1

 

 2. 25x²+70x+49-9=0

  25x²+70x+40=0 (/5)

 5x²+14x+8=0

D=14²-4*5*8=196-160=36=6² 

  x_{1}=(-14-6)/2*5=-20/10=-2

x_{2}  =(-14+6)/10=-8/10=-4/5=-0,8

 

3.  1/4x²-3x+9-1=0

1/4x²-3x+8=0 

 D=(-3)²-4*9*1/4=9-9=0

x_{1}= x_{2} =3/2*(1/4)=3/(1/2)=6

 

4. 1/9x²+10/3x+25-16=0

  1/9x²+10/3x+9=0 (/3)

1/3x²+10x+3=0

D=10²-4*3*1/3=100-4=96=( 4 корня из 6 ) ²

 

x_{1}=(-10- 4rкорня из 6)/(2*(1/3))= (-10- 4 корня из 6 ):(2/3) = (-3(10+ 4 корня из 6 )/2 

x_{2}=(-10 + 4 корня из 6)/(2*(1/3))= (-10 + 4 корня из 6 ):(2/3) = (-3(10 4 корня из 6 )/2